CREATIVE LEADERSHIP OF EDUCATIONAL INSTITUTION ADMINISTRATORS UNDER SARABURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Taksaworabut, Nattapong; Laosawatdikul, Phatsayakorn; Chulasukhont, Phuwadon (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to 1) to study the creative leadership of educational institution administrator under the Saraburi Primary Education Service Area Office 1, and 2) to compare the creative leadership of educational institution administrator under the Saraburi Primary Education Service Area Office 1, classified by gender, work experience, and school size. This is a preliminary research study. The sample group consists of 300 school administrators and teachers under the Saraburi Primary Education Service Area Office 1 for the academic year 2024, selected through stratified random sampling. The research tool used is a questionnaire with a reliability coefficient of 0.947. The statistical methods used for data analysis include percentage, mean, standard deviation, t-test, and one-way ANOVA. The research results showed that: 1) the overall creative leadership of school administrators under the Saraburi Primary Education Service Area Office 1 is at a high level. When considering individual aspects, the teamwork aspect had the highest average score, followed by flexibility and adaptability, vision, creativity, and consideration for individuality, respectively. 2) The creative leadership of educational institution administrator under the Saraburi Primary Education Service Area Office 1, when classified by gender, work experience, and school size, showed no statistically significant differences at the .05 level.